Oracle Database Exadata Cloud Service : a beginner's guide - Spendolini, Brian (New York : McGraw-Hill Education, 2019)
"Quickly install, configure, and start using Oracle Database Exadata Cloud Service with the hands-on information contained in this comprehensive Oracle Press guide. Designed for easy learning, the book features real-world examples, detailed illustrations, and step-by-step instructions. Oracle Database Exadata Cloud Service: A Beginner's Guide walks you through the basics and shows you how to provision, create, and deploy databases. Basic system administration tasks, including data backup and recovery, software patching, and system updating, are clearly explained. Advanced monitoring and data compression techniques are also covered"--
The Oracle Database Exadata Cloud Service -- Creating an Oracle Database Exadata Cloud Service -- The Exadata Cloud Service UI -- Exadata Cloud Services Tooling and CLIs -- Smart scans and storage indexes -- Compression techniques -- Exadata resource management -- Exadata smart flash cache -- Managing and monitoring the Exadata Cloud Service -- TDE location.
Includes index.
Keywords: Oracle (Computer file); Cloud computing; Database management